A Feminist Literary Critique of Women's Resistance to Patriarchal Culture in Laksmi Pamuntjak's Amba and Its Pedagogical Relevance as a Teaching Module - Pasaribu, Christin; Hadiansyah, Firman; Senjaya, Arip (The Future of Education Journal, 2025)
This study aims to analyze and describe women's resistance to patriarchal culture in the novel Amba by Laksmi Pamuntjak. It employs Karen Horney’s psychoanalytic feminist theory to examine the types of female resistance. According to Horney’s theory of resistance, there are three forms: moving toward others, moving against others, and moving away from others. Women engage in these three types of resistance as a response to patriarchal culture that hinders their careers, education, and lives. This research uses a qualitative descriptive method to describe women’s resistance. Data collection techniques include documentation, reading, and note-taking. Data analysis is conducted using descriptive analysis techniques. The instrument used is a data card. This study also discusses the relevance of its findings as a teaching module based on the Merdeka Curriculum to enhance literature learning in schools.